Development of automatic temperature and humidity control systems for eggs incubators with internet of thing technology - Poolwan, Jittapoo; Sripan, Boonyarit; Kingthong, Sanyaluck (RMUTSB ACADEMIC JOURNAL, 2021)
Development of an automatic egg incubator system, the researcher applied internet of things (IoT) technology to control operation conveniently and efficiently. In this research, the operating system was designed and divided into 2 parts, including part of processor inside the incubator, and part of processor on smartphone devices and data communication in the processing of the system within the egg incubator via the server for the storing space of status from the sensors of the climate control system in the egg incubator. The climate control system inside the incubator was processed by the Raspberry Pi as the processor. It served to read the value from the sensor inside the egg incubator for controlling the heating and humidification inside the egg incubator and sent the sensor data to the server stored in NoSQL format. This research developed a system to process on the Android operating system by designing user interface for convenience and simplification that users can easily use and control the operation anywhere with the internet access. The egg incubator prototype was (width×length×height) 50×50×60 centimeters with incubation capacity of 56 eggs. This research evaluated the processing efficiency of the prototype for properly process according to the specified weather conditions and can work for a long period of time without error. For the working part on smartphone, it can read the sensor values and control the incubator's operation correctly.